Cationized gelatin hydrogels mixed with plasmid DNA induce stronger and more sustained gene expression than atelocollagen at calvarial bone defects in vivo. Issue 5 (23rd March 2016) - Komatsu, K.; Shibata, T.; Shimada, A.; Ideno, H.; Nakashima, K.; Tabata, Y.; Nifuji, A.
Abstract: Gene transduction of exogenous factors at local sites in vivo is a promising approach to promote regeneration of tissue defects owing to its simplicity and capacity for expression of a variety of genes. Gene transduction by viral vectors is highly efficient; however, there are safety concerns associated with viruses. As a method for nonviral gene transduction, plasmid DNA delivery is safer and simpler, but requires an efficient carrier substance. Here, we aimed to develop a simple, efficient method for bone regeneration by gene transduction and to identify optimal conditions for plasmid DNA delivery at bone defect sites. We focused on carrier substances and compared the efficiencies of two collagen derivatives, atelocollagen, and gelatin hydrogel, as substrates for plasmid DNA delivery in vivo . To assess the efficiencies of these substrates, we examined exogenous expression of green fluorescence protein (GFP) by fluorescence microscopy, polymerase chain reaction, and immunohistochemistry. GFP expression at the bone defect site was higher when gelatin hydrogel was used as a substrate to deliver plasmids than when atelocollagen was used. Moreover, the gelatin hydrogel was almost completely absorbed at the defect site, whereas some atelocollagen remained. When a plasmid harboring bone morphogenic protein 2 was delivered with the substrate to bony defect sites, more new bone formation was observed in the gelatin group than in the atelocollagen group. These results suggested that the gelatin hydrogel was more efficient than atelocollagen as a substrate for local gene delivery and may be a superior material for induction of bone regeneration.